A comparative study on the pore-size and filter type effect on the molecular composition of soil and stream dissolved organic matter. (August 2017) - Denis, Marie; Jeanneau, Laurent; Pierson-Wickman, Anne-Catherine; Humbert, Guillaume; Petitjean, Patrice; Jaffrézic, Anne; Gruau, Gérard
Graphical abstract: Highlights: Comparative study of DOM isolated using two filter types and two pore size filters. No pore size or filter type effect was observed on bulk scale descriptors. No filter effect was observed on the distribution of the 43 target molecules. Possibility to compare molecular results for different filter type and porosity. Breakup of colloids due to forces applied during filtration at 0.2 µm. Abstract: Biogeochemistry of dissolved organic matter (DOM) is important to ecology, ecotoxicology and the carbon cycle. DOM is operationally defined as the OM fraction that passes through filters. Since different filter pore-sizes, ranging from 0.2 to 0.7 μm, are commonly used, it is necessary to test if this choice has an effect on the concentration and composition of DOM in order to ensure the comparison between studies using different filter pore sizes and filter types (cellulose acetate vs glass fibre). The concentration and composition of DOM was investigated along a soil-river continuum in a lowland headwater catchment using two filter pore sizes (0.2 and 0.7 μm). Dissolved organic carbon (DOC) was quantified, and the DOM composition was investigated using spectroscopic (specific UV absorbance) and isotopic (δ 13 C) bulk-scale descriptors and semi-quantitative molecular analysis by thermally assisted hydrolysis and methylation with tetramethylammonium hydroxide coupled to a gas chromatography and mass spectrometry (THMGC-MS). No significant differences were detected between DOM < 0.2 μm and DOM < 0.7 μm for bulk scale descriptors. Moreover, at the molecular scale, the distribution of the 43 targeted compounds was not impacted. However their concentrations were slightly higher in the < 0.2 μm fraction. This could be due to a shield effect of mineral phases in the < 0.7 μm fraction implying a decrease in their recovery. Consequently, the DOM studies using 0.7 and/or 0.2 μm filters can be compared. This similarity between those two pore-sizes is suggested to be due to the breakup of colloids by shear forces applying locally during filtration performed at 0.2 μm.